(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
The growing demand for mobile internet and wireless multimedia applications has motivated the development of broadband wireless-access technologies in recent years. There are several issues that could impact the base station handover as a serious problem in the mobile communication system. In hard handover, a short time break known as handover interruption decreases the quality-of-services (QoS) due to connection between mobile subscriber station (MS) and serving base station (BS) is closed and ranging hand initiation to establish new connection. Prolonged time of request and response due to number of neighbours to scan will cause delay in handover process. This research proposed performance analysis of WiMAX/IEEE 802.16 with mobility supported to scan the channels provided by the mobile station. The proposed strategy required the mobile station for operation with a scan that can be used to reduce the time when trying to establish a network connection or do between neighboring base station handover. A second type is the fast handover that is proposed to reduce the unnecessary surrender to six different access modes. The mobile WiMAX air interface utilizes orthogonal frequency division multiple access (OFDMA) as the preferred multiple-access method in the downlink (DL) and uplink (UL) for improved multipath performance and bandwidth scalability. All simulations are run using MATLAB software to develop a new Overlay Scanning Mechanism (OSMA) algorithm. OSMA mainly focus on when to perform a scan to estimate future needs. Simulation results are expected to show WiMAX coverage by using real world data to detect movement and show that there are strategies that reduce the time required for scanning operations significantly.